Pengaruh Kompetensi Mahasiswa Akuntansi Terhadap Konvergensi International Financial Reporting Standards (Studi Kasus pada Perguruan Tinggi Swasta di Semarang) (Students' Journal of Accounting and Banking, 2014)
This research aim was to determine the effect of Accounting Students competence on IFRS Convergence. Respondents in this study were as many as 352 respondents. Using regression analysis to determine the relationship between variables Accounting Students competence toward IFRS Convergence. The test results showed that the Accounting Student competence had positive and significant impact on IFRS ConvergenceKeywords: Accounting Students Competence and IFRS Convergence